If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(4n + -5h) = 0 Reorder the terms: 7(-5h + 4n) = 0 (-5h * 7 + 4n * 7) = 0 (-35h + 28n) = 0 Solving -35h + 28n = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-28n' to each side of the equation. -35h + 28n + -28n = 0 + -28n Combine like terms: 28n + -28n = 0 -35h + 0 = 0 + -28n -35h = 0 + -28n Remove the zero: -35h = -28n Divide each side by '-35'. h = 0.8n Simplifying h = 0.8n
| x+0.86(x+0.01)=0.052 | | 3x-10+4x-20= | | X-yi=8-4i | | 4x+35=3+8x-8 | | 2x-7/4=3x-6/8 | | 13x-4y=47 | | 5-(5^2)/1(-4)= | | -1(x^2-4x-77)=0 | | 6x+17=7x+12 | | 5-(5^2)/1(-4) | | 9=6+3u | | x+0.57(x+0.01)=0.0493 | | 5x+15+4x-6=360 | | R=J+Y+Z | | 7x-9-4x=4x-2 | | 12y-3=3 | | 0=-7y-28 | | y=1/1x-2 | | -4(3M-8)+13(M-4)=15-8 | | 25Y+35X=1450 | | 6x+6=-8+4x+20 | | 2ln(cos(x))=f(x) | | 7x(x)-19=4x(x)+29 | | x+77+2x+73+51=360 | | -10=13y | | 4(2y-3)=(3y+6) | | 5Y-4(Y-2)+5=13 | | x+92+x+52+2x=360 | | 35X+25Y=1450 | | 1296t=-16(t-9)(t+9) | | 9565=x^2-5x+65 | | 4x+18=5x-26 |